Determinação da atividade aeróbia específica de lodo de ETE por respirometria - Koyashiki, Rafael Seiji (2016)
Biological treatments for aerobic processes should create and maintain a favorable environment for reproduction and growth of microorganisms involved in the degradation of organic matter. In the aerobic respiration process the microorganisms is based on the decomposition of the substrate in the presence of oxygen, the consumption of the substrate by the microorganisms transforms the organic matter into more stable end products such as carbon dioxide, water and new cells. The respirometry is the measurement and interpretation of aerobic respiration rate of the biomass, defined as the amount of oxygen that is consumed, or the production of CO2 by microorganisms per unit volume and time. The respirometry is a technique that can be used for monitoring, based on the analysis of oxygen consumption or carbon dioxide production originating from the metabolic activity of the microorganisms. This follow-up treatment and remediation systems enables the improvement of aerobic processes used. In this research work, was desired evaluate the aerobic biological activity of sludge microorganisms of ETE in the removal of carbonaceous organic matter of dairy effluent through a respirometric system on bench scale. The degradation rate of organic matter by carbonaceous aerobic microbial community in this work was named as a specific aerobic activity (SEA). The reduction efficiency of the organic load in the experiment fostered by aerobictreatment by the activated sludge process has reached up to 88% of the total COD. The SEA of the sludge microorganisms was 0.0206 to 0.2290 mg CO2 / mg SSV. h. Through this work, it can be verified that the respirometry is an effective tool in achieving the biomass present behavior data in aerobic sludge and low response time.